Anthropometrics Indices, physical fitness and activity level among Batek children in Taman Negara Kuala Tahan, Pahang / Mohd Hafizuddin Baki - Baki, Mohd Hafizuddin (2016)
A cross-sectional study related to anthropometric indices, physical fitness and activity level among Batek and Rural Malay children was carried out in Taman Negara, Pahang, Malaysia. The study included a total of 128 children, 80 male and 48 female. Participants were children between the ages of 9 and 12 years old. Anthropometric measurements such as height, weight and waist-to-hip ratio were taken. Body mass index (BMI) was used as a measure of obesity and to describe nutritional status. Children were classified into four body mass categories (underweight, normal weight, overweight and obese) based on the International Obesity Task Force's age and gender specification definitions. Nutritional status was determined by the distribution of the z-score of eight for age (WAZ), height for age (HAZ), and weight for height (WHZ), from the WHO growth chart of reference. Pedometer worn over three days measured children's activity level. Batek childrens prevalence 20.4 % are overweight and 28.8 % are obese. Prevalence of malnutrition (stunting and wasting) among Batek children for both genders is high. Due to inadequate or imbalanced energy consumption among the children, a comprehensive effort in the health care program is essential for both populations to improve their nutritional status.